Surgical treatment of Eagle’s Syndrome through intraoral access: a case report and literature review - Bezerra, Rodrigo Cristhian Avelino; Gusmão, Jonas Nogueira Ferreira Maciel; Silva, Bruno Frota Amora; Alves, Rodrigo Lemos; Santos, Eliardo Silveira; Rêgo, Roberto Dias (Brazilian Journal of Case Reports, 2021)
The styloid process is a bone projection that originates in the tympanic portion of the temporal bone. The enlongation of the styloid process, or the ossification of the styloid process, can originate a series of symptoms such as dysphagia, odynophagia, facial pain, otalgia, headache, tinnitus and trismus, establishing the clinical picture of Eagle Syndrome. In this report, we present an important clinical case of adult patient diagnosed with Eagle’s Syndrome who underwent surgery for reduction of the enlongated styloid process, by intraoral approach, added to a literature review study.